PENGARUH AUDIT FEE, INSTITUTIONAL OWNERSHIP DAN LITIGATION RISK TERHADAP KUALITAS AUDIT DIMODERASI DENGAN KOMITE AUDIT - Aldo Rompas; Sukrisno Agoes (Jurnal Kontemporer Akuntansi, 2024)
This study aims to determine how the effect of audit fees, institutional ownership and litigation risk on audit quality by moderating audit committees in manufacturing industries listed on the Indonesia Stock Exchange during 2015-2019. The sample selected by purposive sampling method and valid data are 30 companies. The data processing technique uses multiple regression analysis assisted by the Eviews (Enocometric Views) version 10 program and Microsoft Excel 2016. The results of this study indicate that litigation risk has a significant effect on audit quality, and the audit committee increases its influence on audit quality. The implication of this research is that the audit quality produced by the auditor will increase if the company has a high litigation risk.